The impact of spasticity and contractures on dependency and outcomes from rehabilitation - Stephen Ashford; Barbara Singer; Hilary Rose; Lynne Turner-Stokes (The Journal of the International Society of Physical and Rehabilitation Medicine, 2022)
Background: Acquired brain injury (ABI) can result in severe physical impairment causing difficulty with moving which, if not actively managed, can lead to contracture and deformity. Delayed access to rehabilitation may result in more contracture, with potential to increase duration of rehabilitation, cost and therapy time required. Objective: Describe the amount of therapy input for patients undergoing specialist in-patient rehabilitation following ABI, the differences in the type of therapy received by people with and without contracture and/or spasticity, and the impacts on functional outcomes including care needs and cost of care. Materials and Methods: A cohort analysis of prospectively collected data from 426 patients with ABI in a UK tertiary inpatient rehabilitation program. The Neurological impairment Scale (NIS) was used to identify the presence of spasticity or contracture. The Northwick Park Therapy Dependency Assessment (NPTDA) was used to calculate the therapy hours and type of treatment provided to people with and without spasticity and/or contracture. Outcomes (change in function and independence) were compared including the UK Functional Assessment Measure (UK FIM+FAM). Results: The Male/Female ratio was 63:37% with a mean age: 44.0(SD 13) years and a mean length of stay in specialist inpatient rehabilitation: 103 (SD 49) days. Aetiology: Stroke (63%), Trauma (20%); Hypoxia (7%): Other (10%). Patients with contractures were significantly more dependent than those without, both on admission and discharge. They stayed on average 31 days longer (95%CI 21.1, 40.5) (P=0.001) with an additional mean episode cost of £25,588 (95%CI £18.085, 34,043) (P<0.001). Despite this, they made similar overall functional gains resulting in similar long-term savings in the cost of ongoing care. Conclusion: Routine collection of the NPTDA supported quantification of the impact of spasticity and contracture on therapy inputs, length of stay, functional gains, and costs. People with contractures following ABI require more therapy time in rehabilitation to achieve similar functional gains, but nevertheless were cost-efficient to treat.